Identifying IBD Providers' Knowledge Gaps Using a Prospective Web-based Survey. Issue 9 (26th February 2020) - Malter, Lisa; Jain, Animesh; Cohen, Benjamin L; Gaidos, Jill K J; Axisa, Lisa; Butterfield, Lori; Rescola, Becky Johnson; Sarode, Sudha; Ehrlich, Orna; Cheifetz, Adam S
Abstract : This article details the recent survey conducted by the Crohn's and Colitis Foundation of their members to identify IBD knowledge and resource gaps to inform future educational programming. Abstract: Background: As treatments, management strategies, and the role of advanced practice providers (APPs) have evolved in recent years, the Crohn's & Colitis Foundation sought to understand the educational and resource needs of clinicians caring for patients with inflammatory bowel diseases (IBDs). The aim of this study was to describe the self-identified IBD knowledge and resource gaps of clinicians to inform the development of future programming. Methods: A survey containing 19 questions created by the foundation's Professional Education Committee, a subset of its National Scientific Advisory Committee, was conducted from September 7, 2018 to October 15, 2018. Responses were included from providers if they were currently seeing any IBD patients in a clinical setting. The foundation distributed the survey by email and various social media channels to encourage a diverse response. The survey included questions on comfort levels around diagnosis, treatment, and management of patients with IBD, in addition to preferences and utilization of educational resources. The × 2 test was used to evaluate significant differences among respondents in the various domains surveyed. Results: There were 197 eligible responses, of which 75% were from MD/Dos, followed by 25% APN/PA/RN/MSN/PhD/other; and 70% of respondents provide care for adult patients. The amount of time in practice was divided evenly among respondents. Fifty-seven percent of respondents practice in an academic/university setting, and approximately 75% indicated that ≥21% of their practice consisted of patients with IBD. Forty-four percent and 46% of respondents reported access to IBD based mental health providers and social workers in their practice, respectively. Seventy-two percent reported access to radiologists, 69% had access to dietitians, and 62% had access to advance practice providers. The areas of greatest educational need were prescribing medical cannabis (if approved locally) for pain management (62%); caring for patients with prior malignancy (35%); caring for pregnant patients and family planning (33%); caring for elderly patients (30%); and therapy decisions, including use of JAK inhibitors (29%), drug holidays (25%), and use of biosimilars (24%). More than 50% of respondents stated they do not participate in shared decision-making, citing time as the most common limiting factor. The majority of providers cited live education as their preferred learning format, and they wish to earn continuing medical education (CME) hours. Conclusion: This survey helped identify current IBD educational needs in our professional community. With a rapidly changing treatment landscape and an increase in the diversity of providers delivering care, additional opportunities to keep abreast of practice changes are critical to providing comprehensive, quality care in IBD. Our survey demonstrated that shared decision-making is underutilized in practice due to a need for resources that aid in its efficient integration into practice. Based on our results, a focus on creating live learning opportunities that offer CME are needed in the areas of therapeutic decision-making and treating IBD in special subsets (eg, prior malignancy, pregnancy, elderly).